MENINGKATKAN HASIL BELAJAR SISWA PEMBELAJARAN IPA MATERI ENERGI PANAS DAN PENGARUHNYA DALAM KEHIDUPAN SEHARI-HARI MELALUI METODE EKSPERIMEN - Yanti .; Barita Esman Dabukke (Fakultas Ilmu Pendidikan Universitas Sari Mutiara Indonesia, 2019)
The purpose of this study is to improve student learning outcomes of natural science learning material heat energy and its effects in everyday life at SD Negeri 066652 Bakti Luhur T.A 2018/2019. This type of research is a classroom action research conducted II cycle, each cycle including planning, implementation, observation, and reflection. This research was conducted at 066652 Public Elementary School devoted to the subjects of class III research students, amounting to 20 students. From the results of the cycle I teacher activity sheet scored 72.72 with sufficient criteria while the cycle I student activity sheet got a value of 54.54 with less criteria and the results of the cycle II teacher activity sheet scored 79.54 with good criteria while the cycle II student activity sheet get a score of 81.81 with very good criteria. Based on the results of learning tests in the first cycle, of the 20 students there were 11 students who completed the percentage of 55% and obtained an average value of 65 and in the second cycle of 20 students there were 18 students who completed the percentage is 90% and an average value of 81 is obtained. From the student learning outcomes can be concluded that through The Method Experiments can improvingstudent learning outcomes in learning science heat energy material and its effect in daily life at SD Negeri 066652 Bakti Luhur TA 2018/2019.